UVB-Induced Skin Autoinflammation Due to Nlrp1b Mutation and Its Inhibition by Anti-IL-1β Antibody - Murase, Yuya; Takeichi, Takuya; Koseki, Jun; Miyasaka, Yuki; Muro, Yoshinao; Ohno, Tamio; Shimamura, Teppei; Akiyama, Masashi (Frontiers in Immunology, 2022)
NLRP1 (NACHT and leucine-rich repeat containing protein family, pyrin domain containing 1) is an innate immune sensor to form an inflammasome complexes. NLRP1 hyperactivity has been reported to cause inherited autoinflammatory diseases including familial keratosis lichenoides chronica and NLRP1-associated autoinflammation with arthritis and dyskeratosis. We generated Nlrp1b (the mouse homologue of human NLRP1) gain-of-function knock-in (Nlrp1b KI) mice with UVB irradiation-induced autoinflammatory skin lesions. We demonstrated that UVB irradiation induces IL-1β upregulation and IL-1β-dependent inflammation via caspase-1 activation in these Nlrp1b KI mice. RNA sequencing revealed the upregulation of inflammasome pathway-related genes, keratinocyte stress marker genes, and keratinocyte differentiation marker genes in the Nlrp1b KI mice after UVB irradiation. The skin inflammation and hyperkeratosis from UVB irradiation in the Nlrp1b KI mice were inhibited by both intraperitoneal and subcutaneous administration of anti-IL-1β antibodies before UVB irradiation. UVB irradiation and the IL-1β pathway are important in the pathogenesis of NLRP1-associated autoinflammatory skin lesions.